Advanced Urologic Cancer Consensus Conference (AUC3) 2025: Expert consensus on the management of renal cell and urinary tract cancers - Rana R. McKay; Sumanta Pal; Wanling Xie; David Aggen; Laurence Albiges; Andrea Apolo; Michael B. Atkins; Rick Bangs; Kathryn E. Beckermann; Joaquim Bellmunt; Stephanie A. Berg; Mehmet A. Bilen; et al. (CA: A Cancer Journal for Clinicians, 2026)
Abstract The therapeutic landscape for renal cell carcinoma (RCC) and urinary tract cancer (UTC) has transformed dramatically, creating complexity in treatment selection and sequencing. The 2025 Advanced Urologic Cancer Consensus Conference was convened to establish evidence‐based expert consensus recommendations for optimal management. A multidisciplinary panel of 51 experts participated in a modified Delphi process addressing questions developed through iterative consensus‐building covering RCC and UTC management. Voting occurred before and after the conference, and analyses focused on postmeeting responses. Consensus was defined as ≥75% agreement, with strong consensus as >90%. Strong consensus was found on the use of adjuvant pembrolizumab for higher risk RCC (pathologic T2 [pT2], grade 4; pT3–pT4, any grade; pTXN1; or fully resected metastatic disease) and on neoadjuvant therapy before cystectomy for localized UTC. There was strong consensus on the use of enfortumab vedotin plus pembrolizumab as frontline therapy for metastatic UTC and the use of platinum‐based chemotherapy postprogression in biomarker‐negative UTC. For RCC, there was consensus on the role of single‐agent vascular endothelial growth factor receptor–tyrosine kinase inhibitor therapy after progression on frontline immune checkpoint inhibitor/vascular endothelial growth factor receptor–tyrosine kinase inhibitor therapy or dual immune checkpoint inhibitor therapy. However, there was a lack of consensus on other critical areas in the management of RCC and UTC. The 2025 Advanced Urologic Cancer Consensus Conference provides evidence‐informed guidance for complex clinical scenarios while identifying critical research priorities. The group recognizes that the lack of consensus across multiple areas highlights the need for improved patient selection and prospective studies enabling optimal combination and sequencing approaches. This iterative annual process will address evolving treatment paradigms to optimize outcomes.